Morphometric and physical characteristics distinguishing adult Patagonian lamprey, Geotria macrostoma from the pouched lamprey, Geotria australis - Baker, Cindy F. (2021)
The pouched lamprey, Geotria australis Gray, 1851, has long been considered monotypic in the Geotriidae family with a wide southern temperate distribution across Australasia and South America. Recent studies have provided molecular and morphological evidence for a second Geotria species in South America; Geotria macrostoma (Burmeister, 1868). The aim of this study was to determine morphometric and physical characteristics of adult G. macrostoma that further differentiate this re-instated species of Geotriidae from G. australis. The diagnostic features discriminating immature adult G. macrostoma from G. australis when entering fresh water, are distinct differences in dentition, oral papillae and fimbriae counts and differences in coloration. In addition, G. macrostoma display greater growth of the prebranchial region and oral disc and has a deeper body depth and higher condition fac tor. All current ecological knowledge of the genus Geotria is based on Australasian popula tions, which may not be applicable to G. macrostoma. To ensure the conservation and protection of the Patagonian lamprey as a re-identified species, further investigations are needed to understand its life history, biology and ecology throughout its range.